Iron homeostasis and pulmonary hypertension: iron deficiency leads to pulmonary vascular remodelling in the rat - Zhao,L (Circulation Research, 2015)
Rationale: Iron deficiency without anemia is prevalent in patients with idiopathic pulmonary arterial hypertension and associated with reduced exercise capacity and survival.Objectives: We hypothesized that iron deficiency is involved in the pathogenesis of pulmonary hypertension and iron replacement is a possible therapeutic strategy.Methods and Results: Rats were fed an iron-deficient diet (IDD, 7 mg/kg) and investigated for 4 weeks. Iron deficiency was evident from depleted iron stores (decreased liver, serum iron, and ferritin), reduced erythropoiesis, and significantly decreased transferrin saturation and lung iron stores after 2 weeks IDD. IDD rats exhibited profound pulmonary vascular remodeling with prominent muscularization, medial hypertrophy, and perivascular inflammatory cell infiltration, associated with raised pulmonary artery pressure and right ventricular hypertrophy. IDD rat lungs demonstrated increased expression of hypoxia-induced factor-1α and hypoxia-induced factor-2α, nuclear factor of activated T cells and survivin, and signal transducers and activators of transcription-3 activation, which promote vascular cell proliferation and resistance to apoptosis. Biochemical examination showed reduced mitochondrial complex I activity and mitochondrial membrane hyperpolarization in mitochondria from IDD rat pulmonary arteries. Along with upregulation of the glucose transporter, glucose transporter 1, and glycolytic genes, hk1 and pdk1, lung fluorine-18–labeled 2-fluoro-2-deoxyglucose ligand uptake was significantly increased in IDD rats. The hemodynamic and pulmonary vascular remodeling were reversed by iron replacement (ferric carboxymaltose, 75 mg/kg) and attenuated in the presence of iron deficiency by dichloroacetate and imatinib, 2 putative treatments explored for pulmonary arterial hypertension that target aerobic glycolysis and proliferation, respectively.Conclusions: These data suggest a major role for iron in pulmonary vascular